Delectable : sweet & savory baking - Fleming, Claudia; Young, Catherine D. (Random House, 2022)
"Claudia Fleming's The Last Course and her menus from Gramercy Tavern introduced us to her sophisticated, classically inspired seasonal desserts and pastries. Her distinctive dishes established a new standard in pastry kitchens across the country. Now, bakers in home kitchens everywhere, and at every level, can rejoice knowing that this all-new collection from an absolute master has been written specifically for them. Here they will find inspiration from the recipes Claudia developed, tweaked, and perfected in her very own kitchen. Each recipe reflects her signature style and skilled approach in an even more personal way. Recipe inspirations include those passed down from her mother (and reworked and improved upon), those from Claudia's travels, and those that truly brought her comfort or satisfied a craving. Claudia's incredible knowledge and techniques from a storied career in pastry and dessert inform these more comfortable, casual, delicious desserts and savory bites. Throughout the book are helpful and comprehensive essays covering topics such as Working with Yeast, Layer Cake Tricks, and more. With 143 recipes, the book is organized into chapters including: Breads, Muffins, and Biscuits: Focaccia Bread; Date Nut Muffins with Coconut; Rhubarb Scones Donuts and Cakes: Cider Doughnuts; Apple Crumb Cake; Devil's Food Cake Cookies: Grapefruit Rugelach; Pizzelles Pies: Nectarine and Fig Tart; Plum Cobbler Savories: Eggplant Caponata Tart; Chickpea Crackers Custards, Semifreddos, and a Souffle: Pistachio Semifreddo Fruit: Poached Quince; Candied Orange Rind Pantry: Basil Oil; Sugared Macadamia Nuts; Brown Butter Crumble"--